2013
DOI: 10.15560/9.4.771
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton of the northern coastal and shelf waters of the Yucatan Peninsula, southeastern Gulf of Mexico, Mexico

Abstract: Based on long-term monitoring (2001-2012) and four oceanographic cruises (2010-2012) in the coastal and shelf waters of the Yucatan Peninsula, SE Gulf of Mexico, a list of 306 strictly phytoplanktonic and tychoplanktonic species from 131 genera is presented: centric diatoms (83 species), raphid diatoms (47), araphid diatoms (22), Dinoflagellata (124), Cyanoprokaryota (18), Ebriacea (2), Chlorophyceae (3), Dictyochophyceae (2), Euglenophyceae (2), Cryptophyceae (1), Prymnesiophyceae (1), and Raphidophyceae (1).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 13 publications
2
6
0
3
Order By: Relevance
“…Although these two heterotrophic and unarmored genera were occasionally found in this study, some individuals showed large dimensions (e.g., >200 μm in diameter for Noctiluca ); hence, only a few cells per liter could be suffient to yield significant carbon biomass for these organisms. Large specimens of Noctiluca scintillans (~300–2,000 μm in diameter) have been previously reported in coastal waters of Veracruz and Tabasco [ 3 ] and in continental shelf waters of the Yucatan Peninsula [ 15 ]. Besides, considering the important role of this species in other marine ecosystems as a consumer of some potentially toxic algal blooms [ 45 ], its carbon content and biomass estimated in this work may be useful for trophic ecology studies in SGoM waters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these two heterotrophic and unarmored genera were occasionally found in this study, some individuals showed large dimensions (e.g., >200 μm in diameter for Noctiluca ); hence, only a few cells per liter could be suffient to yield significant carbon biomass for these organisms. Large specimens of Noctiluca scintillans (~300–2,000 μm in diameter) have been previously reported in coastal waters of Veracruz and Tabasco [ 3 ] and in continental shelf waters of the Yucatan Peninsula [ 15 ]. Besides, considering the important role of this species in other marine ecosystems as a consumer of some potentially toxic algal blooms [ 45 ], its carbon content and biomass estimated in this work may be useful for trophic ecology studies in SGoM waters.…”
Section: Resultsmentioning
confidence: 99%
“…Both were represented mostly by small-sized and low-carbon-content genera, such as the unarmored dinoflagellates Gymnodinium and Gyrodinium , and the diatoms Nitzschia and Navicula ( Fig 6 ). These genera have been frequently recorded in different seasons of the year in several regions of the SGoM ecosystem [ 7 , 8 , 11 , 15 , 18 , 31 ]. Although both groups have a low carbon content per cell ( S2 Fig ), the high abundance of Gymnodiniales made a significant contribution to total dinoflagellate biomass (47–64% of total carbon), while pennate diatoms only made as much as 25% of total diatom biomass ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…The highest density and diversity were registered at the westernmost stations (i.e. stations 3 and 6), which are framed by the three marine inlets and featured environmental conditions most similar to marine ones (Ghinaglia, Herrera-Silveira, & Comín, 2004;Merino-Virgilio, Okolodkov, Aguilar-Trujillo, & Herrera-Silveira, 2013). Marine salinity, the potential exchange of water with the sea and the presence of considerable proportions of subaquatic vegetation that provide a broad spectrum of habitats (Giangrande, 1988;Hernández-Alcántara et al, 2011) may interact to explain such fauna patterns.…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86] However, data recorded for the Veracruz Reef System indicated a greater concentration of dinoflagellates in December and January, mainly of species of the genera Protoperidinium and Dinophysis. [87,88] These authors recorded the presence of Dinophysis ovum, a species that was also recorded in great swarms in the northern GM in January and February of 2008.…”
Section: Relationships Between Dms Dmspd and Dmspp And Chlorophyll-mentioning
confidence: 99%